Treatment Outcomes and Costs at Specialized Centers for the Treatment of PTSD After the War in Former Yugoslavia - Priebe, Stefan (Array, 2010)
Posttraumatic stress disorder (PTSD) is a frequent consequence of war experience, and specialized centers have been established in some war affected areas to provide treatment. This study aimed to assess treatment costs and outcomes in such centers in former Yugoslavia. An observational study was conducted in four specialized treatment centers (in Serbia, Croatia, and Bosnia-Herzegovina). A total of 526 consecutive adult patients with war related PTSD were assessed at the beginning of treatment, and 463 met inclusion criteria, including a diagnosis of PTSD on the Clinician-Administrated PTSD Scale for DSM-IV (CAPS). For most patients seven years had elapsed between the traumatic experience and treatment at the specialized center. Service costs were also assessed. Outcomes measured at one year were the presence of a PTSD diagnosis and severity of symptoms as indicated by the CAPS score and subjective quality of life as measured by the Manchester Short Assessment of Quality of Life. At 12 months 380 (72%) patients were followed up, and 325 (86%) met criteria for PTSD. Symptoms and quality of life showed overall small but statistically significant improvements. treatment costs for patients with and without PTSD at 12 months did not significantly differ (€307 and €284, respectively). Conclusions: The recovery rate among patients treated in specialized centers for war-related PTSD several years after the war was poor (14%, and symptom improvements were small. The recovery rate was not linked to service costs. Improving recovery rates might require different treatment methods or different service models.